Internal auditors’ characteristics, internal audit effectiveness, and enterprise risk management in jordan: a resource-based view - Jaber, Taha Ahmad; Shah, Sabarina Mohammed; Mustapha, Mazlina; Johari, Jalila; Tesfagebreal, Gebrehans Mebrahtu (Universiti Putra Malaysia, 2024)
Jordanian public-listed companies (PLCs) face significant internal, external pressures and risks that hinder their performance and survival in today’s high-risk business environment. The relatively recent implementation of Enterprise Risk Management (ERM) adds to its ineffectiveness, further complicating the situation. This study aims to examine the impact of internal auditors’ characteristics on ERM effectiveness and internal audit effectiveness (IAE) from the Resource-Based View (RBV) perspective. Additionally, it explores the relationship between IAE and ERM effectiveness, as well as the mediating role of IAE. A quantitative cross-sectional research design was utilised, collecting data from Jordanian PLCs via questionnaires, with 119 final responses analysed using SPSS and SmartPLS softwares. The findings indicate that internal auditors’ characteristics positively impact both ERM effectiveness and IAE. Furthermore, IAE positively impacts ERM effectiveness and serves as a partial mediator in this relationship. These results align with the RBV, highlighting that internal auditors’ characteristics and IAE as valuable internal resources that foster sustainable competitive advantage. Practical implications include raising companies’ awareness of the critical importance of internal auditors’ characteristics and IAE, thereby offering a cost-effective solution to enhance ERM effectiveness.